Streaming versus edukacja. O jakości i uważności w edukacji oraz streamingu - Grodź, Iwona (Pedagogika Społeczna Nova, 2024)
Education and streaming – this is a combination of technology and pedagogy that is transforming the way we learn and teach others. Streaming – the live transmission or sharing of video content over the Internet – offers new opportunities for education, both formal and informal. The purpose of the essay is to point out several key aspects of this connection that allow us to reveal both the advantages of education via streaming and its disadvantages. Research question: Is streaming really an effective educational method? By enabling free contact with any amount of content, does it create orders of production and reception subject to educational, economic and even ideological requirements to the same extent? Methodology: analysis of scientific discourse on the topic under study.